Effects of stacking method and strain on the electronic properties of the few-layer group-IVA monochalcogenide heterojunctions. Issue 52 (23rd August 2018) - Hu, Yonghong; Mao, Caixia; Yan, Zhong; Shu, Ting; Ni, Hao; Xue, Li; Wu, Yunyi
Abstract : We studied the effect of stacking method and biaxial strain on the electronic properties of the few-layer group-IV monochalcogenides heterojunction. Abstract : Group-IV monochalcogenides (GeSe, SnSe, GeS, SnS) are a class of promising monolayer materials for nanoelectronic applications. However, the GeSe monolayer is the only direct semiconductor in the group-IV monochalcogenides, which limits their application in nanoelectronic fields. Stacking is usually a good strategy to design two-dimensional (2D) materials with novel properties. Taking these monolayer monochalcogenides as basic building blocks, various van der Waals (vdW) heterojunctions can be constructed by different stacking methods. In this study, we systematically investigated the structures, stabilities and electronic properties of thirty-six few-layer group-IV monochalcogenide heterojunctions. All the vdW heterojunctions are proved to be stable. The degree of stability of the few-layer heterojunctions is found to increase with the number of layers. The band gap values of heterojunctions are dependent not only on the components, but also on the stacking order. Five novel 2D direct semiconductors (SnSe/GeSe, GeS/SnS, SnSe/GeSe/SnSe, SnS/GeSe/SnSe and SnS/GeSe/SnSe) are obtained. It's found that biaxial strain can not only tune the values of band gap, but also change the type of the 2D materials. The band gaps of the heterojunctions monotonically increase with the increasing strain and most few-layer heterojunctions transform between direct and indirect semiconductors under biaxial strain. Five heterojunctions (SnSe/GeSe, GeS/SnS, GeSe/SnSe/SnS, SnS/GeSe/SnSe and GeSe/SnS/GeS/SnSe) are found to remain as direct semiconductors under tensile strain (0–0.1). Since the band gaps of these heterojunctions are easy to control in a suitable range, they may have potential applications in nanoelectronic fields.